2021
DOI: 10.1108/cms-03-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

How China’s internet commonweal platform improves customer participation willingness? An exploratory study of Ant Forest

Abstract: Purpose The purpose of this paper is to investigate the influence of internet commonweal characteristics on consumers’ participation willingness, mainly predicated on the stimulus-organism-response model. Furthermore, co-creation value is tested as a mediator of the relationship between internet commonweal characteristics and consumers’ participation willingness, by using the project of Ant Forest issued by Ali-pay as an example. Design/methodology/approach An online questionnaire survey was conducted among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Which means each one has the same weight in the calculations (Balcı, 2011). Specifically, to ensure the representativeness of the sample of this research, we collected the data via “Sojump,” the most representative online crowdsourcing platform in China, which offers similar functions to Amazon Mechanical Turk (Shen et al , 2021). In all, 800 Chinese consumers consisting of 100 consumers for each of the eight groups (cells) participated in our online questionnaire in exchange for a compensation of 6 RMB for each participant, from January 20, 2021, to February 10, 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Which means each one has the same weight in the calculations (Balcı, 2011). Specifically, to ensure the representativeness of the sample of this research, we collected the data via “Sojump,” the most representative online crowdsourcing platform in China, which offers similar functions to Amazon Mechanical Turk (Shen et al , 2021). In all, 800 Chinese consumers consisting of 100 consumers for each of the eight groups (cells) participated in our online questionnaire in exchange for a compensation of 6 RMB for each participant, from January 20, 2021, to February 10, 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment perspectives of verbal ad messages Schreuder et al (2016) conclusively identified two sensory information assessment perspectives stemming from the environment-human interaction [or Stimulus(S)-Organism (O)-Response(R)] model, which has been extensively adopted in discussions of consumers' responses to external multisensory cues in both brick-and-mortar and online shopping environments (Shen et al, 2021). From the internal perspective, environmental stimuli (S) rouses consumers' related emotional experiences, including feelings and behavioral intentions (O), and then finally results in approach or avoidance behaviors (R).…”
Section: Congruence Types Of Nonverbal Ad Messagesmentioning
confidence: 99%
“…Secondly, within the S-O-R model, when consumers accept multisensory input from the external environment, such as COVID-19, the internal state of consumers will also affect their approach or avoidance actions ( Eroglu et al, 2003 ). Some researchers use S-O-R model to explain consumption behaviors stimulated by various external environments, and some predictions have been made by using S-O-R model ( Russell and Mehrabian, 1974 ; Shen et al, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…EA is an individual's tendency to protect the environment and can be reflected by the person's standpoint or view on a specific and detailed environmental problem [37]. On the one hand, the environmental information and activities provided by the platforms can deepen users' understanding and perception of environmental problems [38] and encourage users to establish a correct EA. On the other hand, the negative news about environmental pollution and resource shortage posted by these platforms can arouse users' emotional resonance, which could make users feel anxious and nervous [39].…”
Section: The Mediating Role Of Environmental Attitudementioning
confidence: 99%